Subcellular one carbon metabolism in cancer, aging and epigenetics - Bernasocchi, Tiziano; Mostoslavsky, Raul (Frontiers in Epigenetics and Epigenomics, 2024)
The crosstalk between metabolism and epigenetics is an emerging field that is gaining importance in different areas such as cancer and aging, where changes in metabolism significantly impacts the cellular epigenome, in turn dictating changes in chromatin as an adaptive mechanism to bring back metabolic homeostasis. A key metabolic pathway influencing an organism's epigenetic state is one-carbon metabolism (OCM), which includes the folate and methionine cycles. Together, these cycles generate S-adenosylmethionine (SAM), the universal methyl donor essential for DNA and histone methylation. SAM serves as the sole methyl group donor for DNA and histone methyltransferases, making it a crucial metabolite for chromatin modifications. In this review, we will discuss how SAM and its byproduct, S-adenosylhomocysteine (SAH), along with the enzymes and cofactors involved in OCM, may function in the different cellular compartments, particularly in the nucleus, to directly regulate the epigenome in aging and cancer.